Morbidity and mortality weekly report, Vol. 10, no. 39, For release October 6, 1961 - Communicable Disease Center (U.S.); United States Dept. of Health, Education, and Welfare Public Health Service
Provisional information on selected notifiable diseases in the United States and on deaths in selected cities for week ended September 30, 1961 -- Number of deaths in selected cities Poliomyelitis -- Hepatitis Epidemiological reports: Influenza - 1960-61 -- Poliomyelitis - New York State Pneumonia-Influenza deaths in 108 U.S. cities Table 1. Cases of specified notifiable diseases: continental United States -- Table 2. Cases of specified notifiable diseases: United States, each division and state, and Puerto Rico, for weeks ended October 1, 1960 and September 30, 1961 -- Table 3. Deaths in selected cities by geographic division -- Table 4. Deaths in selected cities